Sailing through social LA GRRAACCEESS: tool for deconstructing and facilitating reflective and reflexive practice. Issue 5 (2nd September 2016) - Smith, Jan
Abstract: Reflective and reflexive practice has become an integral component of practitioner professional training, particularly within professions associated with psychology and nursing. One way of facilitating reflective and reflexive practice is to integrate sensitivity of social interrelated constructs and social differences in relation to Gender, Race, Religion, Age, Abilities, Class, Culture, Ethnicity, Education, Sexual orientation and Spirituality as outlined in the GRRAACCEESS acronym. Inspired from the eighteen-century sailing vessel replica ' La Grace ', this paper extends Burnham's original GRRAACCEESS acronym by adding 'Language' and 'Anatomy' to form the 'LA GRRAACCEESS' model. This paper explores the merits and implications of the LA GRRAACCEESS model in order to assist practitioners with unravelling or deconstructing reflective practice and encourage ongoing mindful reflective practice.